Sustainable environment through treatment of domestic sewage using MFC. (2021) - James, Chippymol; Hema Meenal, S.; Elakkiya, S.; Logarshani, S.
Abstract: The two crises that the world is facing nowadays is energy and waste management. A Microbial fuel cell (MFC) is a collective solution of these two crises. A Microbial fuel cell (MFC) is a bio-electrochemical system that drives electric current and biogas by harnessing the power of bacteria and by mimicking bacterial interaction to convert the organic waste matter. Now this cell is set-up using a double or two chamber systems. MFC converts energy of an electrical force linking atoms (chemical bond) of organic waste into electricity with the aid of microorganism using the redox reactions. Also from domestic waste water containment, a renewable energy source-biogas is produced by capturing CO2 and converting it into methane with the aid of electric current and microorganisms. The whole project aims at bringing out maximum voltage and methane from the domestic wastewater.